Biochemical changes induced by salt stress in halotolerant bacterial isolates are media dependent as well as species specific. Issue 1 (2nd January 2016) - Joghee, Nidhya Nadarajan; Jayaraman, Gurunathan
ABSTRACT: Halophilic bacteria respond to salt stress by regulating the cytosolic pools of organic solutes to achieve osmotic equilibrium. In order to understand the metabolic regulation of these organic solutes, for the first time, we have investigated the effect of salt on growth and biochemical changes in four major moderately halophilic bacterial strains isolated from a saltern region of the Kumta coast, India. The strains under study were Halomonas hydrothermalis VITP9, Bacillus aquimaris VITP4, Planococcus maritimus VITP21, and Virgibacillus dokdonensis VITP14, which exhibited similar salt tolerance (0% to 10% w/v NaCl) with optimal growth at 5% w/v NaCl. Biochemical analysis showed that the total intracellular organic solutes increased significantly with increasing NaCl concentration in the growth medium, and the compositions of the solutes were dependent on the type of strain and also on the nutrient richness of the growth medium. Glutamic acid levels increased in all the strains under salt stress, indicating the significance of glutamic acid as the anionic counterpart of K + /Na + ions and precursor for other synthesized nitrogenous osmolytes. Though initial studies were performed with thin-layer chromatography, mass spectrometry was used to identify the major solutes accumulated by the strains under salt stress, such as proline (VITP4), ectoine (VITP14 and VITP9), and sugars (VITP21) under minimal medium and glycine betaine (by all the strains under study) under complex growth medium conditions. Such comparative study on the stress-dependent metabolic differences of different microbes, under identical experimental condition, helps to identify possible bacterial sources for the production of industrially important solutes.